1998
DOI: 10.1183/09031936.98.11061342
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and clearance of inhaled 18FDG powder in patients with chronic obstructive pulmonary disease

Abstract: As freon is limited in its use as a generator for aerosol inhalation, powder particles are used as an alternative for inhalation therapy. The pulmonary deposition and clearance of inhaled powder particles was studied by positron emission tomography (PET) in ten patients with chronic obstructive pulmonary disease (COPD) and in five normal controls. The powder, 5 microm in mean diameter, was water soluble and labelled with 2-deoxy-2-[18F]-fluoro-D-glucose (18FDG). Powder inhalation was done with single deep insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Collectively, these data suggest that, in addition to cigarette smoking, other potential explanations should be considered. These include (1) shared genetic susceptibility;26 27 (2) delayed clearance of inhaled carcinogens because of airflow limitation;28 and (3) chronic low-grade lung and systemic inflammation associated with COPD 29. We have found previously that, in patients with COPD, systemic levels of C-reactive protein, a biomarker of systemic inflammation, is associated with a future risk of cancer mortality including those related to extrapulmonary cancers 30.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these data suggest that, in addition to cigarette smoking, other potential explanations should be considered. These include (1) shared genetic susceptibility;26 27 (2) delayed clearance of inhaled carcinogens because of airflow limitation;28 and (3) chronic low-grade lung and systemic inflammation associated with COPD 29. We have found previously that, in patients with COPD, systemic levels of C-reactive protein, a biomarker of systemic inflammation, is associated with a future risk of cancer mortality including those related to extrapulmonary cancers 30.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke contains a number of known carcinogens and a very high concentration of oxidants (18) that in combination induce inflammation leading to DNA damage and mutations in lung and airway tissues. With airflow impairment, patients are not able to fully clear the tobacco carcinogens, thus increasing the opportunity to induce DNA damage and mutations (19). In addition, the chronic and persistent oxidative stress and local inflammation have also been implicated in the pathogenesis of lung cancer (20).…”
Section: Copd Biologymentioning
confidence: 99%
“…Fluticasone, being more lipophilic and thus less water soluble, is more likely to be retained in the lumen of the airways and therefore, has a greater chance of being removed from the airways by mucociliary clearance and cough [11]. These differences in lipophilicity may be particularly relevant in patients with severe COPD because marked airflow obstruction will lead to greater proximal deposition of inhaled drugs [12] and therefore mucociliary clearance. Indeed, previous studies in patients with asthma and airflow obstruction have shown that the systemic exposure of fluticasone is more affected by lung function than budesonide [13,14].…”
Section: Introductionmentioning
confidence: 99%